Interrelations between policymakers' intentions and school agents' interpretation of accountability policy in Israel - Lisa Amdur; Irit Mero-Jaffe (Arizona State University, 2017)
The study examined the interrelations between policymakers' intentions for test-based accountability policy, and school agents' perceptions and actions with regard to this policy. Mixed-methods were used and encompassed 24 policymakers, 80 school principals, 168 teachers and case studies of four schools. New institutional theory, including the concept of "environmental shift" (Powell Di Maggio, 1991) and the metaphor of "coupling" (Weick, 1976), served as the conceptual framework. Findings indicate that the interrelations between intentions, perceptions and actions are mainly tightly coupled. These are discussed by invoking three types of institutional isomorphism (DiMaggio Powell, 1983): coercive, mimetic and normative.